Financiamento imobiliário: uma abordagem por meio da planilha eletrônica Microsoft Excel - GOMES, Ana Paula Oliveira (2023)
Financial Mathematics is very present in our daily lives, such as when we make a purchase with cash or installment payment, or even when we finance a car or property. In this way, the present work aims to present a study on Real Estate Financing, in this context, we will discuss the viable options for the payment Convention.